BNT162b2 mRNA COVID‐19 vaccine booster induces seroconversion in patients with B‐cell non‐Hodgkin lymphoma who failed to respond to two prior vaccine doses. (25th January 2022) - Avivi, Irit; Luttwak, Efrat; Saiag, Esther; Halperin, Tami; Haberman, Shira; Sarig, Ariel; Levi, Sivan; Aharon, Anat; Herishanu, Yair; Perry, Chava
Summary: This prospective study evaluated seroconversion rates in response to BNT162b2 (Pfizer‐BioNTech) COVID‐19 vaccine booster in 44 B‐cell non‐Hodgkin lymphoma (B‐NHL) patients who failed to respond to two prior doses [42 previously exposed to anti‐CD20 monoclonal antibodies (moAbs) including 13 under maintenance treatment]. Seroconversion was obtained in 29.5% of the patients. Longer time from last anti‐CD20 moAb (>6 months) and diagnosis of aggressive lymphoma compared to other, incurable B‐NHLs were associated with increased seroconversion rates (47.8% vs.10.5%, p = 0.019 and 50% vs. 17.9%, p = 0.025 respectively). Thus, seronegative patients with B‐NHL that completed anti‐CD20 therapy more than 6 months prior to the booster have greater chances to achieve seroconversion.